Reproducible research into human chemical communication by cues and pheromones: learning from psychology’s renaissance - Wyatt, TD (Royal Society, 2020)
Despite the lack of evidence that the ‘putative human pheromones' androstadienone and estratetraenol ever were pheromones, almost 60 studies have claimed ‘significant' results. These are quite possibly false positives and can be best seen as potential examples of the ‘reproducibility crisis', sadly common in the rest of the life and biomedical sciences, which has many instances of whole fields based on false positives. Experiments on the effects of olfactory cues on human behaviour are also at risk of false positives because they look for subtle effects but use small sample sizes. Research on human chemical communication, much of it falling within psychology, would benefit from vigorously adopting the proposals made by psychologists to enable better, more reliable science, with an emphasis on enhancing reproducibility. A key change is the adoption of study pre-registration and/or Registered Reports which will also reduce publication bias. As we are mammals, and chemical communication is important to other mammals, it is likely that chemical cues are important in our behaviour and that humans may have pheromones, but new approaches will be needed to reliably demonstrate them.